Hair love - Cherry, Matthew A (Kokila, 2019)
Zuri's hair has a mind of its own. It kinks, coils, and curls every which way. Zuri knows it's beautiful. When Daddy steps in to style it for an extra special occasion, he has a lot to learn. But he LOVES his Zuri, and he'll do anything to make her--and her hair--happy.